Analysis of Internet Media Use of Student Biology Learning Interest During COVID-19 - Sabrina Nuraisyah; Risma Delima Harahap; Dahrul Aman Harahap (Jurnal Penelitian Pendidikan IPA, 2021)
The purpose of this study is to find out the influence of internet media on students' learning interests in State Senior High School 2 South Rantau during Covid-19. Internet media has a very important role to foster students' learning interest during COVID-19. This research is qualitative descriptive research where the data source of this research is students. The tools used in collecting data are questionnaires and documentation. The sampling techniques used in this research are purposive. Samples from this study were students of grade XII Science-1 and XII Science-2, each class of 32 students. The results of the poll for learning interests showed that the utilization of internet media is in a high category of 52.3%. Interest in utilizing internet media to learn is in a very less supportive category of 32.5%. Students' desire to learn was in the less good category of 8.7%. Student involvement in learning is in a very supportive category of 6.5%. The results of this study show that there is a positive and negative impact of internet media on students' learning interests